Psychometric Evaluation of the Hyperacusis Impact Questionnaire (HIQ) and Sound Sensitivity Symptoms Questionnaire (SSSQ) Using a Clinical Population of Adult Patients with Tinnitus Alone or Combined with Hyperacusis - Aazh, Hashir; Hayes, Chloe; Moore, Brian C.J.; Danesh, Ali A.; Vitoratou, Silia (Journal of the American Academy of Audiology, 2022)
Background Hyperacusis can be defined as an intolerance of certain everyday sounds, which are perceived as too loud or uncomfortable and which cause significant distress and impairment in the individual's day-to-day activities. It is important to assess symptoms of sound intolerance and their impact on the patient's life, so as to evaluate the need for treatment and to assess the effectiveness of treatments.Purpose The aim was to evaluate the psychometric properties of the Hyperacusis Impact Questionnaire (HIQ), and the Sound Sensitivity Symptoms Questionnaire (SSSQ). The 8-item HIQ focuses on assessing the impact of hyperacusis on the patient, while the 5-item SSSQ is designed to assess the type and severity of sound intolerance symptoms.Research Design This was a retrospective cross-sectional study.Study Sample In total, 266 consecutive patients who attended a Tinnitus and Hyperacusis Therapy Clinic in the United Kingdom within a 6-month period. Fifty-five percent were female. The average age was 54 years (standard deviation = 16 years).Data Collection and Analysis Data were collected retrospectively from the records of patients held at the audiology department. Audiological measures were pure-tone audiometry and Uncomfortable Loudness Levels (ULLs). Questionnaires administered in addition to the HIQ and SSSQ were: Tinnitus Handicap Inventory, Hyperacusis Questionnaire (HQ), and Screening for Anxiety and Depression in Tinnitus.Results Exploratory factor analysis suggested one-factor solutions for both the HIQ and SSSQ. Multiple-causes multiple-indicators (MIMIC) models showed some small influences of gender but negligible effects of age for both the HIQ and SSSQ. Receiver Operating Characteristic (ROC) analysis showed no significant effects of covariates on the ROC curves. Cronbach's α was 0.93 for the HIQ, and 0.87 for the SSSQ, indicating high internal consistency. Convergent validity was supported by moderate correlations between HQ and HIQ scores and between SSSQ scores and ULLs.Conclusion The HIQ and SSSQ are internally consistent questionnaires that can be used in clinical and research settings.
Keywords: Psychometric properties; questionnaire; hyperacusis; tinnitus